Polite Imperative Structures in the Kaledupa Dialect: An Examination of Wakatobi Language - Rima Rima; Susiati Susiati; La Ode Achmad Suherman (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This research delves into the intricacies of imperative politeness within the Kaledupa dialect of the Wakatobi language (KDWL), focusing on both its forms and influencing factors. By employing a descriptive qualitative approach from a pragmatic perspective, the study meticulously gathers data through observation, moderate participatory recording, and note-taking techniques. The findings indicate that politeness in KDWL imperatives is manifested through several linguistic features: the length of utterances, the structuring of speech where non-imperative information often precedes the imperative command, variations in intonation, and the use of kinesic signals such as gestures. These elements combine to create a nuanced system of politeness that is sensitive to the context in which the imperative is delivered. Moreover, the study identifies a range of social and cultural factors that influence how politeness is expressed in KDWL imperatives. These include power dynamics and social status, which dictate the level of formality and deference required; kinship and social relationships, which influence the degree of familiarity or respect in the language used; and group membership and gender, which further modulate the appropriateness of certain forms. Additionally, the nature of the speech situation, the role of customary institutions, and adherence to cultural norms play significant roles in shaping polite imperatives. Indecisiveness also emerges as a factor, suggesting that the speaker’s confidence can impact the politeness strategy employed. Together, these findings underscore the complex interplay between linguistic and social elements in the KDWL, providing a comprehensive understanding of how politeness is constructed and maintained in this linguistic community.